2014
DOI: 10.7465/jkdi.2014.25.1.195
|View full text |Cite
|
Sign up to set email alerts
|

Goodness-of-fit test for the logistic distribution based on multiply type-II censored samples

Abstract: In this paper, we derive the estimators of the location parameter and the scale parameter in a logistic distribution based on multiply type-II censored samples by the approximate maximum likelihood estimation method. We use four modified empirical distribution function (EDF) types test for the logistic distribution based on multiply type-II censored samples using proposed approximate maximum likelihood estimators. We also propose the modified normalized sample Lorenz curve plot for the logistic distribution ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…For this data set, Kang et al (2010) indicated that the two-parameter half logistic distribution provides a satisfactory fit. In this example, we assume that the underlying distribution of this data is the half-logistic distribution based on the multiply Type I hybrid censoring scheme (i.e.,n = 12, T = 100, r = 11, and a i = 1 ∼ 3, 6 ∼ 12).…”
Section: Real Datamentioning
confidence: 94%
“…For this data set, Kang et al (2010) indicated that the two-parameter half logistic distribution provides a satisfactory fit. In this example, we assume that the underlying distribution of this data is the half-logistic distribution based on the multiply Type I hybrid censoring scheme (i.e.,n = 12, T = 100, r = 11, and a i = 1 ∼ 3, 6 ∼ 12).…”
Section: Real Datamentioning
confidence: 94%
“…Based on a gradually type-II censored sample, Wang (2008) provided an exact confidence interval and an exact test for the scale parameter of the HL distribution. Kang and Park (2005) used several type-II censored samples to construct AMLEs of this scale parameter. Adatia (1997) gave an approximation of the size and location parameters of the HL distribution based on a few order statistics such as (k) for reasonably large doubly censored samples.…”
Section: Hl and Related Contributionsmentioning
confidence: 99%
“…Over several decades, various tests including goodness-of-fit test (Kang et al, 2014;Lee, 2013) using different sources of information from data have been introduced by many researchers. More specifically, some methods exploit sample skewness or/and sample kurtosis (D'Agostino, 1970;D'Agostino and Pearson, 1973;Jarque and Bera, 1981) while other methods use the maximum distance between two distribution functions, i.e., target normal distribution function and empirical distribution function (Kolmogorov, 1933;Lilliefors, 1967Lilliefors, , 1969Smirnov, 1939).…”
Section: Introductionmentioning
confidence: 99%